Water Affordable at Any Cost? For Everybody?. Issue 2 (1st February 2015) - Lafrance, David; Curtis, Tom
Abstract : For decades the municipal water industry has emphasized that water is undervalued. That is an easy thing to do when you think broadly about the past and current price of clean and safe water relative to its benefits. But then, when you think about the crushing infrastructure and regulatory cost challenges we will face over the coming decades and the fact that as the cost of providing water and wastewater services increases so does its price, you might wonder how much longer water will be affordable. We'll have more to say about the idea presented in this article in next month's column.